Six Years Evaluation in Recycling Behaviors After Implementation of Governmental Environmental Awareness Programs (Study Case in Bendungan Village, Indonesia) - Wiradimadja, Dafi Dinansyah; Mori, Hisatsuna; Rizkiah, Riza (Technium Sustainability, 2023)
Environmental issues like erosion and flooding are primarily brought on by human activity. Human aspects must be considered in formulating environmental solutions because most environmental issues are caused by or stem from human activity. Lack of knowledge, a lack of skills, poor health, and a lack of a strong work ethic are all internal factors that contribute to environmental issues throughout Indonesia, including in Bendungan Village. Additionally, one of the factors contributing to the creation of unintentionally environmentally detrimental conduct is a lack of environmental understanding. Waste is one of the issues in this community; because people are unaware of the implications of their actions, they throw garbage into drains and vacant ground. Improving people’s quality of life is one way to solve environmental issues by considering social elements, one of which is through sustainability education and incitement given by the West java Government. Through this concept, citizens are given education about the impact of their previous behavior, one of them is their behavior related to waste. The program also provides economic value to waste so that there is an incentive to maintain the condition of waste managing waste in their village. In order to gather the data for this study, a mixed methods approach (qualitative and quantitative) was used, as well as a review of secondary data, direct observations, and semi-structured questioning. According to this study, the programs showed positive results shortly after the programs are conducted. After 6 years, the evaluation conducted by this study showed that the programs are failing. The obstacles to the program in this village are the lack of facilities that they have, and for cadres to teach people about the environment, the lack of the government to provide formal education for the people and the last obstacle to this program is the economic factor, low amount of sellable garbage such as PET and cans have become a major obstacle in promoting garbage bank, thus lead to failing programs, lead to a conclusion that the programs are not sustainable.